Supporting the Development of Spatial Orientation Skills of Blind People Using Binaural Sounds in VSR Game - Mikułowski, Dariusz; Szuba, Bartosz (Studia Informatica. System and information technology, 2025)
Spatial orientation skills are crucial for the comfortable everyday functioning of blind individuals and affect their physical and mental well-being. Developing spatial orientation is usually carried out through traditional training courses without the support of electronic tools. Training them in a natural city environment, even under the supervision of an instructor, is often a very stressful process for the student. This paper proposes a solution for a simplified city space simulator created as a game using 3-dimensional binaural sounds. This simulator can be used at home to develop basic spatial orientation skills for blind people. While feedback from testing by three blind users was positive, the limited scope of this initial evaluation underscores the need for developing more advanced applications supporting the teaching of spatial orientation to blind users.